P030 Improving patient experience by implementing a new patient pathway to obtain methicillin-resistant staphylococcus aureus decolonisation within the paediatric pre-assessment clinic. Issue 7 (19th June 2019) - Mitchell, Hannah; Brooks, Teresa
Abstract : Aim: To improve patient experience, patient safety and streamline the patient journey when obtaining Methicillin-resistant well as unsafe due to interruption of healthcare professionals on the ward. To determine if this patient journey was a fair representation, questionnaires were distributed to parents/carers attending the pre-assessment clinic regarding the time taken at stages throughout the process and their satisfaction. These were distributed to every cardiac patient attending the clinic over a 4 week period (age 0–16 years). From the results it was concluded that the time could be reduced by patients obtaining MRSA decolonisation within the clinic; either by having a prescriber present or producing a Patient Group Directive (PGD). A PGD was preferred due to cost and workforce availability. A PGD was written, approved and implemented within clinic. To assess the reduction in time and change in patient experience, revised questionnaires are in the process of being distributed, again to every cardiac patient attending clinic over a 4 week period. Results: The initial patient journey took 130 minutes from beginning to end, with the time taken to obtain MRSA decolonisation being 80 minutes. 15 questionnaires were distributed, 9 patients responded (aged 6 months-14 years) with the mean time to obtain MRSA decolonisation being 59 minutes (40–85 minutes). From the 9 that responded, 5 of the comments sections regarding patient experience were left blank. 4 contained dissatisfied comments such as 'very long afternoon with lots of walking' and 'seems silly to interrupt the very busy nurses and doctors for a prescription'. Post PGD 5 questionnaires have been distributed and 3 returned. Journey time has now been considerably reduced with an average time to obtain MRSA decolonisation being 5 minutes; a reduction of 54 minutes. Further responses are expected to support this. Conclusion: The patient experience when obtaining MRSA decolonisation prior to cardiac surgery was far from ideal. The implementation of a PGD has improved this experience and considerably reduced the time the process takes. This applies to all age ranges. A limitation is that only 3 questionnaires have been received post PGD implementation. The aim is that at least 9 questionnaires will be returned in order to compare the time pre and post PGD. It is apparent that interruptions to healthcare professionals on the ward by patients from pre-assessment clinic have stopped, resulting in a safer clinical environment. Further work needs to be undertaken in order to demonstrate this. References: Department of Health. 2016. The NHS Outcomes Framework 2016/17 [online] (accessed 17 Nov 2017). Available from: https://www.gov.uk/government/publications/nhs-outcomes-framework-2016-to-2017 Denton M, Hodgson G. Meticillin Resistant Staphylococcus Aureus (MRSA) Guideline. 2010. Leeds Teaching Hospitals. [online] (accessed 17 Nov 2017]. Available from: http://nww.lhp.leedsth.nhs.uk/common/guidelines/detail.aspx?ID=684